Housing bust, bank lending & employment: Evidence from multimarket banks - Glancy, David (Journal of Banking & Finance, 2021)
Using geographic variation in bank lending, I study how bank real estate losses affected the supply of credit and employment during the Great Recession. Banks exposed to distressed housing markets cut mortgage and small business lending relative to other banks in the same county. This lending contraction had real effects, as counties whose banks were exposed to adverse shocks in other markets suffered employment declines, especially in young firms and bank dependent industries. This credit contraction also caused wages to fall and consumer delinquencies to rise, contributing to subsequent declines in nontradable employment.